(untitled) (BIRDEM Medical Journal, 2020)
Background: Kidney transplantation is the preferred treatment for end stage kidney disease (ESKD). Early post kidney transplant urine volume may correlate with favorable allograft survival. The aim of the present study was to examine the potential changes in urine volume with serum creatinine during post-operative hospital stay period after renal transplantation. Methods: We retrospectively reviewed the medical records of patients who had undergone kidney transplantation at Bangladesh Institute of Research and Rehabilitation of Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh between November 2004 and February 2019. Total patients were 133. Twenty four hour urine volume and serum creatinine levels were measured on day 1, day 5 and day 10 after operation. Correlation was performed by using Pearson correlation test. Results: The mean age of the renal allograft recipients was 36.7±10.3 years with male to female ratio of 2.7:1. The mean 24 hours urine volume on Day 1, Day 5 and Day 10 were 8990±5377 ml, 4860±2074 ml and 4485±1722 ml respectively and serum creatinine levels were 3.5±1.5 mg/dl, 1.6±1.2 mg/dl and 1.5±1.3 mg/dl respectively. Negative correlation were found between the Day 1, Day 5 and Day 10 serum creatinine and the urine volume (r=0.366, 0.507, 0.365 respectively) with significant p values (<0.01) in each group. Conclusion: Although urine volume showed considerable variation in early post renal transplantation, it stabilized by the course of time, which was also negatively correlated with the serum creatinine levels. Birdem Med J 2020; 10(3): 149-151